Atrial Fibrillation and Acute Ischemic Stroke: Evaluation of the Contemporary 2018 National Inpatient Sample Database - Gursukhman D.S. Sidhu, MD; Tarek Ayoub, MD; Abdel Hadi El Hajjar, MD; Aneesh Dhorepatil, MD; Saihariharan Nedunchezian, MD; Lilas Dagher, MD; Keith Ferdinand, MD; Nassir Marrouche, MD (CJC Open, 2022)
Background: Atrial fibrillation (AF) in acute ischemic stroke (AIS) is considered a binary entity regardless of AF type. We aim to investigate in-hospital morbidity and mortality among patients with nonparoxysmal AF–related AIS. Methods: Patients hospitalized for AIS with associated paroxysmal or persistent AF were identified from the 2018 national inpatient sample database. We compared in-hospital mortality, stroke-related morbidity, hospital cost, length of stay, and discharge disposition in patients hospitalized with paroxysmal or persistent AF. Results: A total of 26,470 patients were hospitalized for AIS with paroxysmal or persistent AF. Patient with AIS with persistent AF had a longer hospital length of stay (paroxysmal AF, mean [M] 5.7 days, standard deviation [SD] ±6.8 days; persistent AF, M 7.4 days, SD ±11.9 days, P < 0.001) and in-hospital costs (paroxysmal AF, M $15,449, SD ±$18,320; persistent AF, M $19,834 SD ±$23,312, P < 0.001). Patients with AIS with permanent AF had higher in-hospital mortality (paroxysmal AF, 4.6%, vs permanent AF, 6.2%, P < 0.001). Indirect markers of stroke-related disability, like intracranial hemorrhage (odds ratio [OR]: 1.9, 95% confidence interval (CI): 1.6-2.2), need for gastrostomy (OR: 2.1, 95% CI: 1.8-2.4), and tracheostomy (OR: 3.1, 95% CI: 2.1-4.4) were more associated with AIS from persistent AF. Conclusions: Persistent AF is associated with poor in-hospital stroke-related outcome, possibly due to a worse thrombo-embolic phenomenon. AF pattern may be a harbinger of worse stroke-related morbidity. Résumé: Contexte: La fibrillation auriculaire (FA) dans l’accident vasculaire cérébral (AVC) ischémique aigu est considérée comme une entité binaire, quel que soit le type de FA. Nous voulons étudier la morbidité et la mortalité chez les patients hospitalisés pour un AVC ischémique aigu lié à une FA non paroxystique. Méthodologie: Des patients hospitalisés pour un AVC ischémique aigu accompagné d’une FA paroxystique ou persistante ont été répertoriés à partir d’une base de données d’échantillons de patients hospitalisés à l’échelle du pays en 2018. Nous avons comparé la mortalité à l’hôpital, la morbidité liée à l’AVC, le coût de l’hospitalisation, la durée du séjour et les dispositions du congé chez les patients hospitalisés pour une FA paroxystique ou persistante. Résultats: Au total, 26 470 patients ont été hospitalisés pour un AVC ischémique aigu accompagné d'une FA paroxystique ou persistante. Le séjour à l’hôpital était plus long pour les patients atteints d’un AVC ischémique aigu accompagné d’une FA persistante (FA paroxystique, moyenne [M] de 5,7 jours, écart-type [ET] ±6,8 jours; FA persistante, M de 7,4 jours, ET ±11,9 jours, p < 0,001) et les coûts d’hospitalisation ont été plus élevés dans ce groupe de patients (FA paroxystique, M de 15 449 $, ET ±18 320 $; FA persistante, M de 19 834 $, ET ±23 312 $, p < 0,001). La mortalité à l’hôpital était plus élevée chez les patients atteints d’un AVC ischémique aigu accompagné d’une FA permanente (FA paroxystique, 4,6 % vs FA permanente, 6,2 %, p < 0,001). Des marqueurs indirects d’incapacité liée à l’AVC, comme une hémorragie intracrânienne (rapport des cotes [RC] : 1,9, intervalle de confiance [IC] à 95 % : 1,6-2,2), la nécessité d’une gastrostomie (RC : 2,1, IC à 95 % : 1,8-2,4) ou d’une trachéostomie (RC : 3,1, IC à 95 % : 2,1-4,4) ont été davantage associés à l’AVC ischémique aigu découlant d’une FA persistante. Conclusions: La FA persistante est associée à une issue défavorable liée à l’AVC chez les patients hospitalisés, possiblement en raison d’un phénomène thrombo-embolique aggravé. La forme de la FA peut être annonciatrice d’une plus grande morbidité liée à l’AVC.